Explicit instruction for the development of L2 Spanish pragmatic ability during study abroad. (February 2021) - Hernández, Todd A.
Abstract: This study investigates the effects of pragmatic instruction and short-term study abroad (SA) on the development of apologies in second language (L2) Spanish. Students who spent four weeks in different SA programs in Spain were randomly assigned either to an experimental group ( n = 9) or a control group ( n = 9). Native Spanish speakers from Spain were recruited to provide baseline comparison data. Prior to departure, the experimental group received explicit pragmatic instruction on how to formulate apologies in Spanish. During SA, they performed two task scenarios designed to promote their pragmatic competence. The control group did not receive pragmatic instruction, nor did they perform the tasks. Before departure and during the final week of the program, both groups completed an oral discourse completion task (ODCT) consisting of five apology scenarios. The ODCT data and appropriateness ratings indicate that the experimental group significantly outperformed the control group in three areas of pragmatic development: appropriateness, strategy use, and speech rate. Findings suggest that explicit pragmatic instruction both before and during SA contributes to participants' L2 pragmatic competence.